Case Report: Unresectable recurrent nasopharyngeal cancer treated with immuno oncology - Flauto, Fabiano; Di Crescenzo, Rosa Maria; Damiano, Vincenzo (Frontiers in Oncology, 2025)
BackgroundNasopharyngeal carcinoma (NPC) is a rare epithelial malignancy arising from the mucosal lining of the nasopharynx, with significant geographic prevalence in East and Southeast Asia. Despite advances in diagnostic imaging and treatment modalities, over 70% of NPC cases are diagnosed at advanced stages (III/IV), leading to a high risk of recurrence and metastasis. Conventional salvage treatments for recurrent/metastatic NPC, including radiotherapy and chemotherapy, often demonstrate limited efficacy and poor overall survival outcomes. Recently, immunotherapy has emerged as a promising therapeutic approach, modulating the tumor microenvironment and enhancing the immune system’s ability to target cancer cells. This case report describes an unresectable recurrent NPC treated with immunotherapy, underscoring the potential of immune-based therapies in managing advanced NPC.Case presentationA 51-year-old male, with a medical history of hypercholesterolemia and a right parietal ganglioglioma, presented with undifferentiated, infiltrating non-keratinizing NPC diagnosed in 2022. Initial MRI and PET/CT scans revealed locally advanced disease, prompting induction chemotherapy followed by chemoradiotherapy. Although the patient experienced several chemotherapy-related complications, follow-up imaging indicated significant tumor reduction. He subsequently underwent concurrent chemoradiotherapy, achieving stable disease. In late 2023, recurrence was identified, and biopsy confirmed EBV-positive NPC. A multidisciplinary team evaluated the case, considering options for re-irradiation and surgical intervention. However, due to the tumor’s location and associated surgical risks, the decision was made to initiate first-line systemic therapy with platinum salts and gemcitabine, followed by immunotherapy with Pembrolizumab. Post-chemotherapy assessments revealed undetectable EBV DNA levels and a complete radiological response. Instrumental reassessment confirmed a complete response, with a negative EBV DNA plasma evaluation. The continued success of systemic therapy and close monitoring remained the focus of the patient’s care.ConclusionThis case underscores the complexity of managing recurrent NPC and the importance of a multidisciplinary approach. It highlights the evolving role of immunotherapy in treatment strategies, demonstrating its potential to improve outcomes in recurrent/metastatic NPC. Ongoing research is essential to further advance treatment options for this challenging condition. The patient remains under close follow-up, with surgery considered a potential option, given the sustained radiological response.